Microplastics act as an important protective umbrella for bacteria during water/wastewater disinfection. (15th September 2021) - Shen, Maocai; Zeng, Zhuotong; Li, Long; Song, Biao; Zhou, Chengyun; Zeng, Guangming; Zhang, Yaxin; Xiao, Rong
Abstract: As an important contributor of environmental microplastics, wastewater treatment plants have attracted extensive attention. The negative effect of suspended particulate matter on disinfection effect has also been established. The main aims of this study were to understand the potential effects of granular polyethylene microplastic and fibrous polyamide microplastics on ultraviolet and chlorine disinfection in water/wastewater treatment. In the laboratory, microplastics were exposed to different disinfection methods, which represented the disinfection dose and disinfection conditions of real water and wastewater treatment. Escherichia coli (8099) were selected as the experimental object. Microplastic suspended solids were closely related to water turbidity and UV transmittance at 254 nm. The occurrence of microplastics significantly reduced the efficiency of ultraviolet and chlorine disinfection in water/wastewater treatment, and the efficiency decreased with the increase of microplastics concentration or the decrease of disinfectant dosage. When the concentration of microplastics reached a certain level (>50 mg L −1 ), even if the exposure dose continued to increase, the disinfection efficiency could not be improved. Microplastics can reduce the concentration of disinfectants around them by reacting with disinfectants, thus protecting the microorganisms enriched on the surface of microplastics. Although the harsh conditions tested here are rarely met in a typical water treatment process, it represented a worse result. These results were intended to be used by water treatment plants to predict the effects of microplastics in the secondary effluent on UV and chlorine disinfection processes. Graphical abstract: Image 1 Highlights: Impacts of microplastics on water/wastewater disinfection have been studied. Presence of microplastics reduced the efficiency of UV and chlorine disinfection. Microplastics reduce disinfectant concentration around bacteria by reacting with them.